Fatigue crack initiation in 2024-T3 aluminium alloy - Sarımustafa, Ali. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1983., 1983)
In this thesis "Fatigue-crack initiation in 2024-T3 aluminium alloy was investigated using experimental methods with compact tension specimens having various notch root radius. The root radii are varied from 0.04 to 2.5 mm. The fatigue-crack initiation tests were conducted on a closed loop servo-controlled fatigue testing machine. The loading was tension to tension and frequencies of fatigue tests were 3 Hz. Initiation of fatigue-crack was detected by means of a microscope. The effects of notch root radius on the fatigue-crack initiation was evaluated by using linear-elastic-fracture-mechanics theory. The results of experiments are plotted, discussed and compared with the results of the previous studies.
Keywords: Aluminum alloys -- Fatigue.